2015
DOI: 10.1017/s096025851500032x
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding depression and the cost of inbreeding on seed germination

Abstract: We review the literature on effects of inbreeding depression (ID) on seed germination for 743 case studies of 233 species in 64 families. For 216 case studies, we also review the relationship between mass and germination in inbred vs. outbred seeds. Inbred seeds germinated equally well as outbred seeds in 51.1% of 743 case studies, but better than outbred seeds in only 8.1%. In c. 50.5% of 216 cases, mass of inbred seeds was equal to (38.0%) or larger than (12.5%) that of outbred seeds. The magnitude of ID spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 335 publications
(331 reference statements)
3
41
0
Order By: Relevance
“…We also found that inbred maternal plants produced fewer total seeds than outbred plants, and that maternal plant inbreeding negatively affected the timing and total proportion of seedling emergence. These results are consistent with numerous studies showing that inbred plants generally produce fewer, often smaller, and less viable seeds than outbred plants (Husband and Schemske, 1996;Baskin and Baskin, 2015).…”
Section: Herbivory and Maternal Plant Inbreeding Affect Seed Productisupporting
confidence: 92%
See 1 more Smart Citation
“…We also found that inbred maternal plants produced fewer total seeds than outbred plants, and that maternal plant inbreeding negatively affected the timing and total proportion of seedling emergence. These results are consistent with numerous studies showing that inbred plants generally produce fewer, often smaller, and less viable seeds than outbred plants (Husband and Schemske, 1996;Baskin and Baskin, 2015).…”
Section: Herbivory and Maternal Plant Inbreeding Affect Seed Productisupporting
confidence: 92%
“…Self-fertilization decreases heterozygosity, thereby exposing deleterious recessive alleles to selection and simultaneously decreasing the contribution of overdominance to fitness (Charlesworth and Charlesworth, 1987). Consequently, inbred progeny often exhibit inbreeding depression such as reduced germination and growth, slower development, and decreased reproductive output relative to outbred plants (e.g., Husband and Schemske, 1996;Baskin and Baskin, 2015). Inbred plants also typically show reduced expression of constitutive and induced defense-related traits (Kariyat et al, 2012(Kariyat et al, , 2013Leimu et al, 2012;Campbell et al, 2014), which can result in reduced resistance to herbivores (Carr and Eubanks, 2002;Ivey et al, 2003;Leimu et al, 2008;Delphia et al, 2009; Bello-Bedoy and Núñez-Farfán, 2010; Kariyat et al, 2011).…”
mentioning
confidence: 99%
“…Nevertheless, according to Baskin & Baskin (2015), it did not seem to be a strong relationship between a decrease in germination and an increase in the coefficient of inbreeding (F), in 743 species studied.…”
Section: Resultsmentioning
confidence: 76%
“…). The general perception is that there is no strong relationship between decreasing germination with greater inbreeding coefficient, or between increasing germination and higher population genetic diversity (Baskin & Baskin ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, germplasm should be collected from subpopulations which belong to the same genetic cluster, to maintain or re‐establish the natural gene flow and to avoid outbreeding depression, likely expressed as a reduced fitness of the subsequent generations due to the disruption of gene complexes or of the local adaptation (Vander Mijnsbrugge et al . ; Baskin & Baskin ).…”
Section: Discussionmentioning
confidence: 99%